Design and experimental validation of an annular dielectric elastomer actuator for active vibration isolation - Zhao, Yunhua; Guo, Qiwei; Wu, Song; Meng, Guang; Zhang, Wenming (Mechanical systems and signal processing, 2019)
•Annular dielectric elastomer actuators (ADEAs) are proposed for active vibration isolation.•The parametric dependence of the ADEA is analyzed to provide guidance for compact actuator design.•Active vibration isolation with an ADEA is implemented employing the adaptive feedforward control.•Vibration suppression even with large amplitude disturbance can be achieved when the ADEA acts as the isolator. This paper proposes annular dielectric elastomer actuators (ADEAs) for active vibration isolation. A theoretical model is developed to characterize the actuator and parametrized based on experimental data. The parametric dependence of the natural frequency of the ADEA on the actuator geometry, applied voltage, and the pre-stretch of the elastomer is analyzed. The electromechanical behavior of the ADEA is also characterized experimentally and estimated by finite-impulse-response (FIR) based adaptive filter. Vibration control with the ADEA as the active vibration isolator is implemented by employing the filtered-x least-mean-square (Fx-LMS) algorithm due to incorporating the effect of the secondary path function. The vibration isolation ratios at the 7 and 11 Hz harmonics with the amplitudes of 320 μm and 330 μm are 10.53 and 11.81 dB, respectively. For the isolated mass under the 9 Hz sinusoidal disturbance with peak-to-peak amplitude of 1400 μm, vibration attenuation of 10.74 dB is achieved. The results show that ADEAs have the potential for active vibration isolation systems even with large amplitude disturbance. It provides guidelines for the actuator design and promote the dielectric elastomers (DEs) for engineering applications.